The Creative Phenomenon of Tarık Buğra in the Tradition of the Turkish Novel - Khujaeva Guljahon (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2026)
This article explores the life and literary legacy of prominent Turkish author Tarık Buğra from a scholarly perspective. It highlights his unique portrayal of rural life, complex psychological depth, and the representation of universal values such as justice, courage, faith, and intellect. Buğra’s artistic style is marked by historical realism, inner monologue, narrative dynamism, and deep psychological insight. Furthermore, his socio-philosophical reflections contribute significantly to the development of contemporary Turkish novel writing.